The plant Extracts of Momordica Charantia and Trigonella Foenum Graecum Have Antioxidant and Anti-Hyperglycemic Properties for Cardiac Tissue During Diabetes Mellitus. Issue 5 (2009) - Tripathi, Uma Nath; Chandra, Deepak
Abstract : Oxidative stress is currently suggested to play a major role in the development of diabetes mellitus. There is an increasing demand of natural anti-diabetic agents, as continuous administration of existing drugs and insulin are associated with many side effects and toxicity. The present study was aimed to investigate the effect of Momordica charantia (MC) and Trigonella foenum graecum (TFG) extracts (aqueous) on antioxidant status and lipid peroxidation in heart tissue of normal and alloxan induced diabetic rats. In a 30 days treatment, rats were divided into six groups (I-VI) of five animals in each, experiments were repeated thrice. Administration of MC (13.33 g pulp/kg body weight/day) and TFG (9 g seeds powder/kg body weight/day) extracts in diabetic rats has remarkably improved the elevated levels of fasting blood glucose. A significant decrease in lipid peroxidation (p<0.001) and significant increase in the activities of key antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione-s-transferase (GST) and reduced glutathione (GSH ) contents in heart tissue of diabetic rats were observed (group V and VI) upon MC and TFG treatment. Our studies demonstrate the anti-hyperglycemic and anti-oxidative potential of Momordica charantia and Trigonella foenum graecum, which could exert beneficial effects against the diabetes and associated free radicals complications in heart tissue.